Yoruba Traditions in the Midst of Foreign Influences, A Critical Evaluation - Kola Adekola (Yoruba Studies Review, 2021)
The Yoruba of South west Nigeria pride themselves as a “nation” with a rich cultural heritage. Tis jealously guided heritage believed to have been handed down from ancient times has however suffered greatly from modern influences owing to contacts with foreign cultures. Tis essay highlights the measures to preserve the Yoruba heritage and the militating problems in the light of the unbridled contacts with foreign cultures. The paper also provides evidence to suggest that the Yoruba, just like every other ethnic groups in Nigeria, could have fashioned their own developmental frameworks but for the imposition of foreign ideas/ideals.